2021
DOI: 10.1007/s12262-021-02975-z
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Surgical Education: a Global Perspective

Abstract: Undergraduate surgical education is failing to prepare medical students to care for patients with surgical conditions, and has been significantly compromised by the COVID-19 pandemic. We performed a literature review and undertook semi-structured reflections on the current state of undergraduate surgical education across five countries: Egypt, Morocco, Somaliland, Kenya, and the UK. The main barriers to surgical education at medical school identified were (1) the lack of standardised surgical curricula with ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…These are the competencies of a safe practitioner, not just a surgeon. It appears that this deficit may also exist on an international scale, with the literature describing surgical education as inadequate on a global scale in both more and less economically developed countries 40–42 .…”
Section: Discussionmentioning
confidence: 99%
“…These are the competencies of a safe practitioner, not just a surgeon. It appears that this deficit may also exist on an international scale, with the literature describing surgical education as inadequate on a global scale in both more and less economically developed countries 40–42 .…”
Section: Discussionmentioning
confidence: 99%
“…A survey among physicians and therapists also reported similar ndings. The educational environment during surgical rotations, simulation training, and traditional curricula can signi cantly impact undergraduate students' career decisions (12). Unfortunately, some studies have identi ed de ciencies in structured robotic training curricula and found that robotic operating rooms do not always offer motivating learning environments for medical students (13).…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative care should be covered in its entirety. This is important for aspiring surgeons and future general practitioners and physicians who are likely to manage patients during the pre-operative workup of patients as well as in their post-operative recovery and beyond [3]. The need for multidisciplinary team involvement and effective communication between the different specialities is evident.…”
Section: Introductionmentioning
confidence: 99%
“…However, the learning needs are typically not comprehensively addressed. This is believed to be largely due to the gap between the theory taught and the limitations in practical, experiential learning [3]. Ultimately, this means that new graduates are unfamiliar with the all-encompassing clinical knowledge and skills required in treating patients with 1 surgical conditions.…”
Section: Introductionmentioning
confidence: 99%